2020
DOI: 10.1038/s41598-020-66428-5
|View full text |Cite
|
Sign up to set email alerts
|

Urupocidin C: a new marine guanidine alkaloid which selectively kills prostate cancer cells via mitochondria targeting

Abstract: New bicyclic guanidine alkaloid, urupocidin C (Ur-C) along with the previously known urupocidin A (Ur-A) were isolated from the rare deep-sea marine sponge Monanchora pulchra, harvested in Northwestern Pacific waters. The unique structure of Ur-C was elucidated using 1D and 2D NMR spectroscopy as well as mass spectra. We discovered a promising selectivity of both alkaloids for human prostate cancer (PCa) cells, including highly drug-resistant lines, compared to non-malignant cells. In cancer cells, marine deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 54 publications
0
27
0
1
Order By: Relevance
“…55 For example, the guanidine alkaloid urupocidin A (Ur-A) has cytotoxic activity against different human cancer cell lines (Figure 1). 56 Ur-A inhibits an EGF-induced neoplastic transformation of epithelial cells. It induces a G2/M-phase cell cycle arrest and apoptosis of human cervical carcinoma HeLa cells.…”
Section: Novel Compounds From Other Marine Creaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…55 For example, the guanidine alkaloid urupocidin A (Ur-A) has cytotoxic activity against different human cancer cell lines (Figure 1). 56 Ur-A inhibits an EGF-induced neoplastic transformation of epithelial cells. It induces a G2/M-phase cell cycle arrest and apoptosis of human cervical carcinoma HeLa cells.…”
Section: Novel Compounds From Other Marine Creaturesmentioning
confidence: 99%
“…57 A new bicyclic guanidine alkaloid, urupocidin C (Ur-C), along with the earlier known Ur-A, isolated from the rare deep-sea marine sponge Monanchora pulchra found in North-western Pacific waters exhibit acute selectivity for human prostate cancer cells and are believed to be a novel promising candidates as effective drugs against aggressive and drug resistant cancer of the prostate (Figure 1). 58 Neutrophils play an important role in acute inflammatory responses and recent studies have expanded their role to modulate chronic inflammatory and autoimmune diseases. Several types of chemical drugs are in use to treat inflammatory disorders, but with adverse side effects.…”
Section: Novel Compounds From Other Marine Creaturesmentioning
confidence: 99%
“…(D) Marine alkaloid sourced and guanidine-containing complex capable of targeting mitochondria. Image reproduced with permission, from Ref Dyshlovoy et al (2020) . (E) Snapshot of the permeation of Rh 19 derivative through bilayer lipid membrane (left panel) and schematic diagram of its mechanism (right panel, where R stands for a deprotonated neutral form, and RH + stands for a singly protonated cationic form).…”
Section: Mitochondria-targeting Agentsmentioning
confidence: 99%
“…Both guanidine and biguanide are delocalized lipophilic cationic molecules, which have a delocalized positive charge and therefore exhibit stronger lipophilicity than groups with a localized charge. Some studies have found that a new marine guarantin alkaloid can selectively kill prostate cancer cells and that the cytotoxic effect is related to mitochondrial targeting ( Dyshlovoy et al, 2020 ) ( Figure 3D ). This study confirmed for the first time that mitochondrial targeting is the central mechanism of the anti-cancer effect of these molecules and their derivatives.…”
Section: Mitochondria-targeting Agentsmentioning
confidence: 99%
“…Эффективность этого действия повышалась при их применении с известным препаратом «Олапариб» и одним из основных противоопухолевых лекарств «Доцетаксел». Следовательно, урупоцидин С можно рассматривать в качестве лидерной молекулы для более детальных фармакологических исследований в экспериментальной и клинической онкологии [3].…”
Section: новые биопрепараты для медициныunclassified